2018
DOI: 10.1021/acs.jafc.8b04566
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Engineering of Bacillus paralicheniformis Acid Urease To Degrade Urea and Ethyl Carbamate in Model Chinese Rice Wine

Abstract: Bacillus paralicheniformis urease (BpUrease) has been shown to be a promising biocatalyst for degrading the carcinogenic chemical ethyl carbamate (EC or urethane) in rice wine. However, low EC affinity and catalytic efficiency limit the practical application of BpUrease. In this study, we improved the EC degradation capability of BpUrease by site-saturation mutagenesis (SSM). The best variant L253P/L287N showed a 49% increase in EC affinity, 1027% increase in catalytic efficiency (k cat/K m), and 583% increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…The highest content of flavor substances in both samples was ethyl hexanoate, followed by ethyl caprylate. The content of ethyl hexanoate exceeds 200 mg/L, indicating the high quality of strong-aroma liquor [ 43 ]. Compared with the non-treated sample, the contents of ethyl caproate, ethyl acetate, ethyl valerate, and furfural in the ECH-treated sample were reduced by 108.1 mg/L (from 490.58 ± 16.74 mg/L to 382.48 ± 5.27 mg/L), 6.4 mg/L (from 13.63 ± 1.10 mg/L to 7.23 ± 0.91 mg/L), 8.67 mg/L (from 22.18 ± 2.21 mg/L to 13.51 ± 1.26 mg/L), and 5.36 mg/L (from 13.92 ± 0.25 mg/L to 8.56 ± 0.25 mg/L), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The highest content of flavor substances in both samples was ethyl hexanoate, followed by ethyl caprylate. The content of ethyl hexanoate exceeds 200 mg/L, indicating the high quality of strong-aroma liquor [ 43 ]. Compared with the non-treated sample, the contents of ethyl caproate, ethyl acetate, ethyl valerate, and furfural in the ECH-treated sample were reduced by 108.1 mg/L (from 490.58 ± 16.74 mg/L to 382.48 ± 5.27 mg/L), 6.4 mg/L (from 13.63 ± 1.10 mg/L to 7.23 ± 0.91 mg/L), 8.67 mg/L (from 22.18 ± 2.21 mg/L to 13.51 ± 1.26 mg/L), and 5.36 mg/L (from 13.92 ± 0.25 mg/L to 8.56 ± 0.25 mg/L), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Use of urethanase to directly degrade EC has been proposed, and ongoing experiments are being conducted to determine how well this treatment can scale up. Urethanase can reduce EC in rice wine and soy sauce by 15 to 50% (93,128,211). An alternative approach to direct addition of a purified enzyme is inoculation of beverages with microorganisms possessing degradation activity similar to that of the purified enzymes.…”
Section: Experimental Methods For Mitigation Of Ec In Foods and Bever...mentioning
confidence: 99%
“…Without affecting the flavor of the wine, an appropriate reduction in temperature also helps reduce the EC content in the wine, which is a key adjustment point for EC control from a process perspective ( Hasnip et al, 2004 ). Some studies showed that acid urease catalyzed the decomposition of urea to ammonia and carbon dioxide, decreasing the content of an important precursor of EC in wine ( Cerreti et al, 2016 ; Liu et al, 2018 ; Yang et al, 2021 ). Since 1999, Europe has approved the use of acid urease extracted from fermented LAB in wine ( Cerreti et al, 2016 ).…”
Section: Safety Risks and Countermeasures In Winementioning
confidence: 99%